Sleep quality, functional skills, and communication in preschool-aged children with autism spectrum disorder - Lamônica, Dionísia Aparecida Cusin; Giacheti, Celia Maria [UNESP]; Dias Hayssi Haduo, Michele; Dias dos Santos, Maria Jaquelini; da Silva, Nathani Cristina [UNESP]; Pinato, Luciana [UNESP] (Elsevier, 2021)
Aim: This study aimed to correlate sleep quality, the performance of functional skills (mobility, self-care, and social function), communication, independence, and severity of ASD in children with ASD. Method: 58 children between 3 and 5 years and 11 months old were investigated. The Childhood Autism Rating Scale was applied to determine the severity of autism; the Sleep Disturbance Scale for Children was used to investigate sleep quality, and the Pediatric Evaluation of Disability Inventory to investigate functional abilities and independence of the children. Results: 68.9 % of the children showed indicative of sleep disorders. There was no correlation between the different sleep disorders and communication. Sleep disorders showed a negative correlation with functional performance and a positive correlation with ASD severity. Interpretation: The current study offers an exploration between sleep and functional skills in children with ASD. These findings provide important clinical implications in the diagnosis and intervention process of children with ASD and also stimulate reflections on the importance in minimize the impact of sleep disorders and functional abilities on the quality of life of these individuals and their families.
Keywords: Autistic disorders; Child development; Communication; Self care; Sleep; Social skills